Pengembangan E-LKPD Berbasis SETS Untuk Meningkatkan Aktivitas Belajar Siswa Sekolah Dasar - Ela Suryani; Zulmi Roestika Rini (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
The purpose of this study was to develop the electronic student worksheets (E-LKPD), based on the Science, Environment, Technology, and Society (SETS), in improving the learning activities of elementary school students. In this Research and Development (R&D) designed research, the data collection techniques used were the questionnaires, tests, and documentation. The data was analyzed with SETS elements, the e-worksheet validity test was measured by the experts validation, the learning practices were measured using the student and teacher observations lists, the effectiveness of the e-worksheet was tested using the independent sample t-test and the students' cognitive mastery test scores. The results showed that the SETS -based e-worksheet was valid, practical, and effective in increasing students’ learning activities. It can be concluded that: 1) the e-worksheet is valid as the average score from the expert validation resulted 93.5% in a ‘very good’ category and can be used without revision; 2) the e-worksheet is practical, proved by the observation result in the experimental class students that reached  88%, compared to the control class with 72 % score. The results of the students’ responses scored 81% in ‘good’ category and 93% in the experimental class in a ‘very good’ category; 3) the e-worksheet proved to be effective shown by the t-count which was higher than the t-table (2.619 > 1.995), that made the H0 was rejected, that suggested there was a difference in the result of cognitive learning in the experimental (91.4% ) and control class (80%).